RIVALITAS ELITE PURI DALAM POLITIK (STUDI KASUS: RIVALITAS ELITE PURI UBUD, PURI PELIATAN, DENGAN PURI GIANYAR DALAM PEMILUKADA TAHUN 2012-2018) - Ari Brahmanta, Ida Bagus Ananta; Ali Azhar, Muhammad; Noak, Piers Andreas (JURNAL ILMIAH SOSIOLOGI: SOROT, 2021)
This study to determine elite Puri Ubud, Puri Peliatan, and Puri Gianyar compete in the Gianyar Pilbup 2012-2018. This research uses conflict theory from Ralf Dahrendorf with qu alitative descriptive method, uses primary and secondary data. The results of the research are: first, the rivalry that occurred was an old rivalry and was repeated in the 2012 Gianyar Pilbup, which at that time also showed that the political struggle between brothers was won by the elite of Puri Gianyar. Second, the defeat of the Puri Peliatan elite made the Puri Ubud elite take a political rol e fight the Puri Gianyar elite in the 2018 Pilbup and another victory wa s won by Puri Gianyar. The defeat of Puri Peliatan and Puri Ubud was due to the lack of character, party ba se. In addition to clan stakes, party bases a lso dominate this conflict, PDIP (Pu ri Gianyar) and Golkar (Puri Ubud and Puri Peliatan). Keyword : Rivalry, Elites Puri, Regional Head Election, Gianyar Regency, Year 2012-2018